Examine the Distant and Near Visual Outcomes after Phacoemulsification with Implantation of Accommodating versus Standard Intraocular Lenses (Medical Forum Monthly, 2024)
Objective: To compare the visual outcomes after phacoemulsification with implantation of crystalens HD and Tek-clear as accommodating intraocular lenses versus SA60AT as standard intraocular lenses.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Ophthalmology, DHQ Hospital Batkhela from July 2016 to December 2018.Materials and Methods: A total of 36 eyes were enrolled. Patient’s ages were > 35 years. Patients demographic were examined after taking informed consent. All the eyes were equally divided into three groups and implanted with three different intraocular lenses. Group A contains 12 eyes with crystalens HD, Group B contains 12 eyes with Tek-clear and Group C contain 12 eyes with SA60AT. Corrected, uncorrected and distant near visual acuity, near point of accommodation, spectacle freedom and satisfaction of patients were examined at 12 weeks postoperatively and compare the results between all groups.Results: At follow up all the patients showed significant improvement in corrected distant visual acuity among all the groups. Uncorrected near visual acuity and distant corrected near visual acuity showed better outcomes in patients implanted with crystalens HD and Tek-clear. Near point of accommodation was closest in the crystalens HD group with p-value 0.002. Patients implanted with accommodating intraocular lenses showed better results regarding spectacle freedom and satisfaction with their near vision as compared to standard intraocular lenses.Conclusion: The crystalens HD and Tek-clear intraocular lenses showed better outcomes regarding near vision and spectacle freedom as compared to monofocal intraocular lens.